Characterization of Terpenoids Phenolic and Coumarin Compounds from Indian Medicinal Plant Holostemma ada kodien and Its Antioxidant Activity. Issue 6 (2nd November 2019) - Deepak, M.; Sulaiman, C.T.; Balachandran, Indira; Subhash Chandran, K.P.
Abstract: Holostemma ada-kodien J.A Schultes is a widely using medicinal plant and its rhizome is being used in various Indian traditional systems of medicines especially Ayurveda. The aim of the present study is to identify the active chemical constituents present in rhizome of H. ada kodien using various chromatographic methods. Various antioxidant tests including ABTS scavenging, Nitric oxide quenching, Ferric reducing and DPPH scavenging assays were carried out on different extracts of rhizome to identify the therapeutically active extraction method. An activity based column chromatographic isolation was carried out in hydro alcoholic extract of H. ada kodien to explore its phytochemical constituents and characterizations of isolated compounds were done using 1 H NMR, 13 C NMR and mass spectrometry. All extracts were given significant results in antioxidant analyses especially the hydro alcoholic extract. The present study led to the isolation of seven compounds out of which four are first report from the plant. The compounds such as lup-20(29)-ene-3β, 28-diol, 3β-hydroxy-12-ursen-28-ic acid, 7-hydroxy-6-methoxycoumarin and 3, 4-dihydroxycinnamic acid were identified for the first time from H. ada kodien and their anti-oxidant activities were analyzed. The identified compounds are found therapeutically active and might be reason behind the beneficial activities of H. ada kodien .